2020
DOI: 10.1097/hco.0000000000000781
|View full text |Cite
|
Sign up to set email alerts
|

Recent trends in acute myocardial infarction among the young

Abstract: Purpose of Review: In recent decades, the incidence of myocardial infarction (MI) has declined among the general population. However, MI rates in the young have not decreased as much as has been observed among older individuals. This review will focus on recent trends of MI in young patients, factors that may account for these trends, and implications for future prevention.Recent Findings: MI rates in young patients, particularly in women, have not decreased in the same fashion as they have for their older cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 43 publications
1
24
0
2
Order By: Relevance
“…However, some populations experience this disease prematurely [ 2 ]. In the last few decades, different studies have shown an increased incidence of CAD in very young people [ 3 , 4 , 5 ], mainly in Asian populations [ 6 ]. Even though they are relatively few in number, these young patients with CAD represent a significant economic and health care burden for society, thus becoming chronic patients [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, some populations experience this disease prematurely [ 2 ]. In the last few decades, different studies have shown an increased incidence of CAD in very young people [ 3 , 4 , 5 ], mainly in Asian populations [ 6 ]. Even though they are relatively few in number, these young patients with CAD represent a significant economic and health care burden for society, thus becoming chronic patients [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several unconventional risk factors such as lipoprotein (a), inflammation, and genetic variations were also found, which may also explain some of the reasons for the early occurrence of MI. 19,20 Our data showed that almost 40% of patients<50 years with a high level of LDL-C over 120mg/dl. Besides, nearly half of these young adults with coronary heart disease are obese.…”
Section: Dovepressmentioning
confidence: 73%
“…In our study, the mean age of admitted NSTEMI patients was 37.34 ± 6.19 years and among them male predominance was prevalent (72.8%, N = 234). Multiple studies have confirmed male as a risk factor of coronary artery disease hence the increased burden of males diagnosed with NSTEMI is already well established 13,14 and is attributed to the protective effects of estrogens in preventing atherosclerosis and prevalence of smoking which was much more common amongst male that has been clearly demonstrated in various epidemiological studies. Although, mean age of these patients are quite younger as most of the studies have documented STEMI in young population rather than NSTEMI that is why data on young population admitted with NSTEMI is limited.…”
Section: Discussionmentioning
confidence: 94%